Types of Slang Words in the Movie Script of Sausage Party - Yoga Darma Putra, I Made (Humanis, 2018)
This paper entitled “Types of Slang Words in Sausage Party Movie Script”is aimed to analyze the types of slang words and their types of meaning found in the Sausage Party movie script. The data were taken from internet on Tuesday September 5, 2017. In analyzing the types of slang words and the types of meaning used, descriptive qualitative method and theory proposed by Allan and Burridge (2006) that consists of five types and supporting theory proposed by Geoffrey Leech (1974) that consists of seven types were used. The result shows that there are fifty slang expressions analyzed in this study. The major slang used in this movie script is formed by two or more words and achieve it own meaning that are different from the source word. The slang meaning found in this study mostly express the implicit meaning of the expression. It can be concluded that Sausage Party movie script has a relatively exclusive language.